The topochemical synthesis of triazole-linked homobasic DNA. Issue 5 (13th November 2015) - Pathigoolla, Atchutarao; Sureshan, Kana M.
Abstract : Triazolyl-DNA ( TL DNA), DNA wherein phosphodiester units are replaced by triazole units, is of great interest. By adopting Topochemical Azide–Alkyne Cycloaddition (TAAC) reaction, we have synthesized homobasic TL DNA oligomers. 5′-ethynyl-3′-azido-2′, 3′, 5′-tri-deoxycytosine, which crystallized with proximal placement of azide and alkyne units of adjacent molecules, underwent TAAC reaction to TL DNA oligomers. Abstract : Triazolyl-DNA ( TL DNA), a DNA-analog wherein phosphodiester units are replaced by triazole motifs, is of great interest. We have synthesized TL DNA oligomers by adopting the Topochemical Azide–Alkyne Cycloaddition (TAAC) reaction. A nucleoside decorated with the azide and alkyne units crystallized with the proximal placement of the azide and alkyne units of the adjacent molecules and underwent the TAAC reaction to form TL DNA oligomers.